Abatacept in subjects who switch from intravenous to subcutaneous therapy: results from the phase IIIb ATTUNE study. Issue 6 (2nd February 2012) - Keystone, Edward Clark; Kremer, Joel M; Russell, Anthony; Box, Jane; Abud-Mendoza, Carlos; Elizondo, Mario Garza; Luo, Allison; Aranda, Richard; Delaet, Ingrid; Swanink, Rene; Gujrathi, Sheila; Luggen, Michael
Abstract : Objective: To assess safety, immunogenicity and efficacy in rheumatoid arthritis (RA) patients switched from long-term intravenous to subcutaneous (SC) abatacept. Methods: In this phase IIIb, open-label, single-arm trial, patients who completed ≥4 years of intravenous abatacept (in long-term extensions of two phase III studies) were enrolled to receive SC abatacept (125 mg/week). The primary objective was safety during the first 3 months after switching from intravenous therapy. Results: 123 patients entered the study (mean Disease Activity Score 28 (based on C reactive protein) and HAQ-DI of 3.4 and 0.94, respectively). At month 3, 120 (97.6%) patients were continuing to receive SC abatacept; no patients discontinued due to lack of efficacy. Adverse events (AEs) were reported in 49 (39.8%) patients through month 3. One patient (0.8%) discontinued due to an AE and one patient (0.8%) experienced a serious AE. Two (1.6%) patients had SC injection site reactions (erythema, pain), both with mild intensity. Clinical efficacy was maintained throughout. Limited impact on immunogenicity was observed when switching routes of administration. Conclusion: These data demonstrate that patients can switch from long-term monthly intravenous abatacept to a weekly fixed dose of 125 mg SC abatacept with no increased safety concerns. This study further supports SC abatacept as an alternative treatment option for patients with RA.